TAM, Emotional Engagement, and Trust on AR Virtual Try-On Behavioral Intention in Shopee - Cahya Ade Ningrum; Muawan Bisri; Fathoni Dwiatmoko (Universitas Darul Ulum, 2026)
The rapid development of digital shopping encourages e-commerce platforms to continue to innovate through the application of immersive technology, one of which is the Augmented Reality (AR) Virtual Try-On (VTO) feature that facilitates consumers in simulating products virtually before purchasing decisions are made. This study was designed to investigate the contribution of Perceived Ease of Use (PEOU), Perceived Usefulness (PU), Emotional Engagement (EE), and Trust (TR) to the Behavioral Intention (BI) of AR VTO feature users in Shopee, Indonesia. The study adopted a quantitative approach through surveying 500 active Shopee users who had used the feature at least once, with data analysis using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method assisted by SmartPLS 4. All instruments were declared valid and reliable based on the results of the outer model evaluation. The four variables were simultaneously proven to have a positive and significant influence on BI. The novelty of this research lies in the simultaneous integration of the cognitive dimensions of TAM, affective, and trust in a single analytical framework applied specifically to the context of Shopee's AR VTO in the Indonesian market, an approach that has not been explored much in the literature before. The research findings have practical implications for Shopee developers in designing a more intuitive, emotionally responsive, and data-secure AR interface, to encourage wider adoption of technology among Indonesian digital consumers.